CFD를 이용한 수윤활 볼베어링의 구름 요소 주위의 마찰 토크분석 - 조준현; 김충현 (한국트라이볼로지학회, 2013)
Water-lubricated ball bearings consist of rolling elements, an inner raceway, an outer raceway, a retainer, and an operating lubricant. In the water environment, ball bearings are required to sustain high loads at high speeds under poorly lubricated conditions. For the analysis of bearing behavior, friction torque is considered as the main factor at various flow rates, rotating speeds, and roughnesses between the rolling element and raceways. When the bearing operates at high rotating speeds, the friction torque between the raceway and rolling elements increases considerably. This frictional torque is an important factor affecting bearing reliability and life cycle duration. For understanding the flow conditions in the inner part of the bearing, this study focuses on the flow around the rotating and revolving rolling elements. A simple model of fluid flow inside the ball bearing is designed using the commercial CFD program ANSYS.